Pengaruh Penggunaan Canva AI dalam Materi Desain Grafis terhadap Peningkatan Motivasi Belajar Siswa Kelas X IPA SMA Muhammadiyah Lempangang - Irwan Aditia; Sukarni Sukarni; Aini Selang; Muhammad Rifal Nawir; Ratih Parica Aleng; Ashilah Munawaroh Arif; Waliullah Akram Afid (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of using Canva AI in graphic design learning materials on the learning motivation of Grade X Science students at SMA Muhammadiyah Lempangang. Low learning motivation in technology-based subjects served as the primary issue underlying this research. The study employed a pre-experimental design using a one-group pretest–posttest model. The research sample consisted of 20 Grade X Science students selected through purposive sampling. Data were collected using a validated learning motivation questionnaire administered before and after the implementation of Canva AI in the learning process. The results showed a significant increase in the average learning motivation score from 58.50 in the pretest to 81.75 in the posttest. Statistical analysis using the paired sample t-test produced a t-value of 47.656 with 19 degrees of freedom, exceeding the critical t-table value at the 0.05 significance level, indicating that the null hypothesis was rejected. These findings confirm that the use of Canva AI has a significant positive effect on students' learning motivation in graphic design materials. Furthermore, Canva AI creates more engaging, interactive, creative, and student-centered learning experiences, making it a promising instructional tool for supporting digital learning and improving educational outcomes among Generation Z students.